Aplikasi Presensi Karyawan Berbasis Web Menggunakan Bootstrap, PHP dan MySQL: Studi Kasus pada Toko Al Jihad - Malik Abdul Aziz; Novita Anggraini (Jurnal Penelitian Multidisiplin Ilmu, 2023)
Information technology (IT) is very useful in all fields, including the field of labor. Labor is everyone who works and produces a result of his work in the form of goods or services. PT Kahatex is a factory engaged in textiles. The employee attendance policy is part of the company's human resource development (HRD) guidelines. The attendance of employees or employees of Toko Al Jihad is still done manually. This activity can cause errors in recording. Therefore, an application is designed to minimize these errors. Employee attendance application design is an application design that can be used to record employee data, employee attendance lists, and to create employee attendance reports. The research methods that the author uses are observation, interviews, literature, and the waterfall method as a system development method. With this employee attendance application, it is hoped that it can help the work in the shop become easier, controlled and organized system. The system used in making this application is the PHP programming language, MySQL database and Bootstrap. So that it can help work at the Al Jihad store to be more effective and controlled.